2005
DOI: 10.1097/00001756-200506210-00015
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 and TRPM8 activation in humans: effects of cinnamaldehyde and menthol

Abstract: The aim of this study was to evaluate the psychophysical effects of both TRPA1 and TRPM8 activation in humans by application of either cinnamaldehyde or menthol. We applied 10% cinnamaldehyde or 40% menthol solutions on the forearm in 10 study participants. Quantitative sensory testing and laser Doppler imaging was performed before and after exposure to the compounds. Cinnamaldehyde evoked significant spontaneous pain and induced heat and mechanical hyperalgesia, cold hypoalgesia and a neurogenic axon reflex e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
204
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(238 citation statements)
references
References 23 publications
30
204
4
Order By: Relevance
“…It is thus possible that vascular responses to these agonists in the current study could be mediated, at least partially, via TRPA1 channels. However, as specific activation of TRPM8 and TRPA1 channels has different vascular effects in human forearm skin (25), it seems unlikely that our responses in either the rat or human study were mediated by TRPA1 channels. Additionally, to date no study has reported the presence of TRPA1 channels in vascular tissues.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is thus possible that vascular responses to these agonists in the current study could be mediated, at least partially, via TRPA1 channels. However, as specific activation of TRPM8 and TRPA1 channels has different vascular effects in human forearm skin (25), it seems unlikely that our responses in either the rat or human study were mediated by TRPA1 channels. Additionally, to date no study has reported the presence of TRPA1 channels in vascular tissues.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, control of the human forearm cutaneous circulation is more complex, having all of these elements active, in addition to sympathetic vasoconstrictor tone (15,17,19,25,33). It is possible that neuronal activation by TRPM8 channels may result in a vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(See, however, Kobayashi et al 2005. ) Studies have also shown that menthol can evoke nociceptive sensations (Green 1992;Cliff and Green 1994;Namer et al 2005) via stimulation of C-fibers (Wasner et al 2004). LTN sites and spots may therefore be attributable to primary afferent fibers that express TRPV1 together with TRPV3 or TRPM8..…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TRPA1 was shown to be a receptor for several pungent compounds, including the active ingredients in wasabi, cinnamon, and uncooked garlic [40,[102][103][104]. Several laboratories have examined the correlation between cold responses and these agonists, with mixed and inconclusive results [40,72,[102][103][104][105]. Thus, a chilly controversy arose regarding the involvement of TRPA1 in thermosensation, one that would presumably be resolved by the study of TRPA1-null mice.…”
Section: Mouse Models Deficient In Temperature Sensingmentioning
confidence: 99%